2019
DOI: 10.1186/s13014-019-1414-x
|View full text |Cite
|
Sign up to set email alerts
|

Radiotherapy in metastatic castration resistant prostate cancer patients with oligo-progression during abiraterone-enzalutamide treatment: a mono-institutional experience

Abstract: BackgroundSome patients experience oligo-progression during androgen receptor targeted therapy (ARTT) treatments. This progression might not indicate a real systemic drug resistance, but a selective monoclonal resistance. With the aim to delay the start of new line treatments we treated oligo-progressive sites with radiotherapy.MethodsFrom June 2011 to Febrary 2019, 29 consecutive metastatic castration resistant prostate cancer (mCRPC) patients were submitted to radiotherapy for oligo-progression (1–3 sites) d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 27 publications
2
22
0
Order By: Relevance
“…However, mCRPC represents a heterogeneous cohort, and an intermediate state between localized and widespread disease may exist in certain patients with mCRPC. Some retrospective studies showed that radiotherapy delayed disease progression in patients with oligometastatic CRPC (17,(25)(26)(27). Similarly, in the present study, CRT was associated with improved PSA response and OS in mCRPC, indicating that patients with limited metastasis might benefit from local therapy against most or all of metastatic lesions.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…However, mCRPC represents a heterogeneous cohort, and an intermediate state between localized and widespread disease may exist in certain patients with mCRPC. Some retrospective studies showed that radiotherapy delayed disease progression in patients with oligometastatic CRPC (17,(25)(26)(27). Similarly, in the present study, CRT was associated with improved PSA response and OS in mCRPC, indicating that patients with limited metastasis might benefit from local therapy against most or all of metastatic lesions.…”
Section: Discussionsupporting
confidence: 79%
“…Increasing evidence indicates that cytoreductive therapy is associated with survival benefits in many metastatic solid tumors, such as metastatic renal cell carcinoma (13,14), metastatic colon cancer (15), and metastatic hormone-sensitive prostate cancer (16). Recently, a retrospective study with a small sample size (n = 29) showed that radiotherapy directed at oligo-progressive sites might prolong the duration of disease control in patients with mCRPC treated with ARATAs (17). However, data to evaluate the value of CRT in patients with mCRPC is still lacking.…”
Section: Introductionmentioning
confidence: 99%
“…New-generation ARAT can result in downregulation of expression of the DNA repair genes, thereby potentiating the effect of ionizing radiation [21]. In clinical studies, a delay of disease progression has been observed after delivering radiotherapy to mCRPC patients treated with abiraterone [22][23][24]. Similarly, our study showed that the survival bene t was most pronounced if cRT was combined with abiraterone.…”
Section: Discussionsupporting
confidence: 60%
“…In contrast, cRT for mCRPC seems less attractive because the value of local therapy at such a late stage is questionable. Several retrospective studies show that radiotherapy to oligoprogressive sites could delay disease progression in mCRPC [22,24,28]. In the study by Yildirim et al, prolonged abiraterone use was also observed in mCRPC patients receiving prostate-directed therapy, but no signi cant improvement of OS was found (24.1 vs. 21.4 months; P = 0.08) [23].…”
Section: Discussionmentioning
confidence: 99%
“…1 Radiotherapy can prolong the control duration of cancer as a frequently adjunctive therapy of surgical surgery and chemotherapy in PCa treatments. 2,3 The appearance of radioresistance severely limits the therapeutic efficacy of radiotherapy, having detrimental influence on the treatment and prognosis of PCa patients. 4 It is essential to enhance the radiosensitivity in PCa to develop the optional selective treatment of PCa.…”
Section: Introductionmentioning
confidence: 99%